Improved electrogeometric model for shielding failure evaluation of double-circuit UHVAC transmission lines based on leader propagation simulations - Ma, Ziwei; Jasni, Jasronita; Ab Kadir, Mohd Zainal Abidin; Azis, Norhafiz; Ma, Yanhua (Elsevier Ltd, 2025)
Both the conventional electrogeometric method (EGM) and leader propagation method (LPM) exhibit deficiencies in predicting the shielding failure (SF) performance of UHV transmission lines (TLs). This paper is dedicated to propose an improved EGM (IEGM) model based on LPM simulations. Firstly, a finite element leader inception and propagation model (FEM-LPM) for lightning attachment to a double-circuit UHVAC TL was developed. Secondly, the effects of operating voltage, downward leader (DL) lateral distance, conductor sag, and terrains on the striking distance (SD) were analyzed using this LPM-FEM model. Simulations show that the operating voltage increases the SD of the ground wire. The increase in DL lateral distance slightly increases the upper phase SD. Increases in both conductor sag and slope cause an increase in exposure width of phase lines, which reduces the SF performance of the TL. Finally, an IEGM model adapted to different slope was proposed based on simulations, and the shielding failure rate (SFR) of the TL calculated based on this IEGM model is close to the field observations of a real case. Due to the lack of more statistics on SFR so far, the model is expected to be validated by more practical cases in the future.